PENGEMBANGAN BAHAN AJAR BERBASIS KOMIK UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA SUB TEMA 2 LINGKUNGAN SEKITAR RUMAHKU : DOI: https://doi.org/10.37850/cendekia.v12i1.78 - Choerul Anwar Badruttamam; Dwi Rosyidatul Kholidah (CENDEKIA, 2020)
The development of thematic teaching materials for comic-based picture stories is one of the tools to help students understand learning. Facts in the field indicate that the learning process has not proceeded as desired, this is because the teacher and students only hold on the textbooks (student books and teacher books) provided by the teacher without being accompanied by supporting media when the teaching and learning process takes place so that children feel bored, unhappy, sleepy and lazy because there are no exciting media to support thematic learning in which there are several subjects. The purpose of this development is to produce products in the form of fun comic-based teaching materials making it easier for students to deepen the understanding of the environment around my home. The kind of research used by researchers is descriptive with qualitative and quantitative data analysis. This type of research is Research and Development, which refers to the Dick and Carrey model. The results of the research development of thematic teaching materials based on pictorial stories meet interesting criteria with the results of the content expert tests reaching 86% eligibility level, design experts reaching 92.5%, linguists reaching 80%, learning practitioners reaching 86%, and the results of field trials reaching 93 %, student learning outcomes on average post-test scores 72.68 and pre-test scores 97. From the explanation above, there are significant differences in student learning outcomes using thematic materials based on comic-based pictorial stories and those who do not use thematic-based thematic teaching materials pictorial. This shows that the product being developed has appropriateness of qualification because the concepts are in accordance with the characteristics of the child. Hence, the teaching material is suitable for use in learning.